Formation of Host-Guest Complexes of 3-(aminomethyl)pyridine HCl Salt and Tetramethylcucurbit[6]uril - FANG ZHAO, FANG; CONG, HANG; TAO, ZHU; FENG XUE, SAI; JIANG ZHU, QIAN (Asian Journal of Chemistry, 2010)
The structure of complex of 3-(aminomethyl)pyridine hydrochloride (AMPY+, guest) and symmetrical tetramethyl substituted cucurbit[6]uril (TMeQ[6], host) has been studied by single crystal X-ray diffraction. UV-vis spectra titration has been employed and the moderate association constants 9.51 × 105 L/mol has been obtained with the interaction models in a ratio of 1:1 between guest and host.